Performance of the artificial urinary sphincter implantation in men with urinary incontinence: Results from a contemporary long‐term real‐world nationwide analysis. Issue 7 (21st July 2022) - Plata, Mauricio; Zuluaga, Laura; Santander, Jessica; Salazar, Milton; Castaño, Juan Carlos; Benavides‐MartÍnez, Johana A.; Garzón, Diana L.; Schlesinger, Ricardo; Serrano, Brigitte; Echeverry, Mariana; Silva, José M.; Varela, Daniela; et al.
Abstract: Purpose: The artificial urinary sphincter (AUS) is one of the most effective surgical treatments for male urinary incontinence regardless of its severity. Current knowledge comes from high‐volume centers, but little is known about the performance of this surgery from community practices. This study aims to report contemporary AUS performance in a nationwide observational study in Colombia. Methods: Male patients who underwent AUS surgery with AMS 800™ between 2000 and 2020 in more than 17 centers and four cities were identified. Pre, intra, and postoperative characteristics were evaluated, mainly addressing patient reported outcomes measurements in the postoperative period. Retrospective and prospective data collection and descriptive analysis were completed. Kaplan‐Meier analysis was used to determine AUS survival rate. Results: Out of an initial 667 cases, a total of 215 patients met inclusion and exclusion criteria and were included. Mean age was 67 ± 9.4 years, and mean follow‐up was 6.0 ± 4.4 years with maximum range of 14 years. The etiology of urinary incontinence was prostate cancer surgery in 141 (81%) of the cases. The rest of the cases were related to benign prostatic disease or spinal cord injury. It is noteworthy that out of 115 patients, only 59 (51.3%) reported previous formal pelvic floor rehabilitation. Subjective severity of urinary incontinence determined by a visual analog scale showed a decrease in 4.5 points after sphincter implantation. Sphincter removal was required in 50 (23.2%) cases. The main reasons for implant removal were urethral erosion and infection. The sphincter survival rate at 2, 5, 8, 10, and 14 years was 76%, 70%, 60%, 57%, and 17%, respectively. Of the subjects at the last follow‐up with the device still in place, 80.7% defined their urinary condition as "does not cause or causes minor discomfort, " and 99% would recommend the device to a friend or relative in the same condition. Conclusions: This series from a community‐based practice shows the lack of adherence to clinical practice guidelines and the lack of standardized data collection. In contrast, this study provides real‐world data on explantation and revision rates, allows physicians to inform patients and to have clear metrics for a shared decision‐making process before the procedure.